1990
DOI: 10.1177/088840649001300310
|View full text |Cite
|
Sign up to set email alerts
|

Why Teachers Are Leaving Special Education

Abstract: This investigation identified the reasons that teachers leave the special education classroom and examined the patterns and trends in teacher dropout in order to help in the retention of quality special educators. A survey instrument was developed and used to determine the factors that teachers identified as to why they left the special education classroom. Survey items were tabulated, and adjusted frequency scores were reported. A contingency analysis determined whether there were associations among any of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Support received from parents has been associated with teacher attrition/ retention. Piatt and Olson (1990) reported that 53% of special educators surveyed indicated that "lack of support" from parents was a reason for attrition. George et al (1992) found that 23% of those BD teachers who intended to stay indicated receiving adequate support from parents, compared to a mere 3% of those who intended to leave.…”
Section: District and School Environmentsmentioning
confidence: 96%
See 4 more Smart Citations
“…Support received from parents has been associated with teacher attrition/ retention. Piatt and Olson (1990) reported that 53% of special educators surveyed indicated that "lack of support" from parents was a reason for attrition. George et al (1992) found that 23% of those BD teachers who intended to stay indicated receiving adequate support from parents, compared to a mere 3% of those who intended to leave.…”
Section: District and School Environmentsmentioning
confidence: 96%
“…Administrators influence the conditions in which teachers work; therefore, it is not surprising that administrative support has been consistently linked to attrition and retention. Lack of administrative support has been associated with attrition among both general (Bloland & Selby, 1980;National Center for Education Statistics, 1991) and special educators (Billingsley 8c Cross, 1991b;Lawrenson 8c McKinnon, 1982;Metzke, 1988;Piatt 8c Olson, 1990). Metzke (1988) found that administrative support was correlated positively with teachers remaining in teaching.…”
Section: District and School Environmentsmentioning
confidence: 96%
See 3 more Smart Citations